Synergy of PERMA No. 3 of 2017 and the 10 Points of the Code of Ethics for Judges in Realizing Fair Trials for Women Facing the Law - Junaidi Syamfran (MASI Mandiri Edukasi, 2025)
This study examines the implementation of Supreme Court Regulation (PERMA) Number 3 of 2017 and the 10-Point Code of Ethics and Guidelines for Judges' Conduct in realizing fair trials for women in Indonesia. Although the principle of gender equality has been normatively guaranteed, trial practice shows that women still face structural and cultural discrimination. A qualitative normative legal approach is used through analysis of documents, legal literature, and court decisions to assess the application of substantive norms and judicial ethics. The results show that PERMA No. 3 of 2017 provides substantive guidelines emphasizing non-discrimination, respect for women's rights, and substantive justice, while the judicial code of ethics serves as a moral foundation that guides judicial behavior. The synergy between these two instruments enhances gender sensitivity in judicial decisions, though its implementation remains influenced by differences in judicial understanding, patriarchal legal culture, and limited resources. This study emphasizes the importance of internalizing ethics and gender sensitivity training as strategies to ensure fair, humane, and non-discriminatory trials.